Subsidizing renewable energy: Higher welfare by lower depreciation costs for fossil power plants? - Sebastian Schäfer (Philipps-University Marburg, School of Business and Economics, 2018)
There is a broad agreement that renewable energy sources (RES) will play an important role to abate CO₂ emissions but there is a contentious debate about the economic sense to promote RES via subsidies. Many static analyses conclude that subsidizing RES ties up capital which could have been used more efficiently by other reduction strategies with lower marginal abatement costs (MAC). Dynamic models, in contrast, emphasize learning effects which lead to lower MAC of RES. In particular a start-up funding to induce an early market entry of RES may be advantageous to benefit from reduced MAC. To our knowledge there has been no attention so far to the effects of renewables' promotion to the necessary shut down of power plants based on fossil energy sources (FES). With respect to the achievement of a certain long-term reduction objective an early market entry of RES allows a longer transition from FES to RES. This also means more time to shut down fossil-based power plants which can reduce respective depreciation costs. We use an endogenous growth model to focus on the trade off between the described decrease of depreciation costs and the capital tie-up of a subsidization of RES. We find that subsidizing RES can indeed lead to a higher welfare solely because of reduced depreciation costs. We conclude that an optimal strategy to reduce emissions should consider both the increase of renewable and the decrease of fossil electricity generation.
Keywords: H23; O21; O44; Q42; Q43; Q48; 330; Renewable Energy; Transition Period; Welfare Effects